PERAN EDUKATOR PERAWAT MELALUI TERAPI NON FARMAKOLOGI DALAM UPAYA MENINGKATKAN KUALITAS TIDUR PASIEN KANKER PAYUDARA - Anggraini, Dian; Marfuah, Dewi; Puspasari, Susy (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Background: Quality sleep is needed by breast cancer patients in order to maintain good physical condition and immune system. Nurses have a role as educators who provide health education. Health education that can be given is non-pharmacological therapy, namely music therapy and PMR to improve sleep quality. Health education for patients is felt to be very important considering that patients are not always hospitalized so that it is hoped that with health education, patients can carry out care independently at home.Methods: The way of implementing community service activities is carried out by exposing non-pharmacological therapies with nurses who are in charge of the chemotherapy room. After being given the material, the selected nurse will apply the therapy to the patient in order to improve the quality of sleep for breast cancer patients who are given chemotherapy.Results: The provision of music therapy and PMR had a positive effect on breast cancer patients undergoing chemotherapy. Most of the patients involved in this service reported an improvement in the quality of sleep.Discussion: Good quality sleep is needed by breast cancer patients to regenerate and repair body cells. Music therapy combined with PMR is effective in reducing physical arousal activity which results in decreased muscle tone so that sleep quality can be fulfilled.